2023
DOI: 10.1021/acsnano.2c12387
|View full text |Cite
|
Sign up to set email alerts
|

All-Water Etching-Free Electron Beam Lithography for On-Chip Nanomaterials

Abstract: Electron beam lithography uses an accelerated electron beam to fabricate patterning on an electron-beam-sensitive resist but requires complex dry etching or lift-off processes to transfer the pattern to the substrate or film on the substrate. In this study, etching-free electron beam lithography is developed to directly write a pattern of various materials in all-water processes, achieving the desired semiconductor nanopatterns on a silicon wafer. Introduced sugars are copolymerized with metal ions-coordinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Notably, the IC 50 (half maximal inhibitory concentration) determined using Hill's equation was as low as 132.8 µg mL −1 for TNF‐α,117.9 µg mL −1 for IL‐1β, 622.6 µg mL −1 for CCL2, and 269.2 µg mL −1 for CCL5, respectively, indicated that Leo@CAT@NM‐Lipo possessed a strong neutralize inflammation ability. [ 25b,37 ]…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the IC 50 (half maximal inhibitory concentration) determined using Hill's equation was as low as 132.8 µg mL −1 for TNF‐α,117.9 µg mL −1 for IL‐1β, 622.6 µg mL −1 for CCL2, and 269.2 µg mL −1 for CCL5, respectively, indicated that Leo@CAT@NM‐Lipo possessed a strong neutralize inflammation ability. [ 25b,37 ]…”
Section: Resultsmentioning
confidence: 99%
“…By significantly reducing the required drug dosage, they enhance treatment efficiency while minimizing systemic side effects. 12 Oral powders, tablets, intravenous injection solutions, and emulsions are currently widely used to enhance drug bioavailability. 13 However, nanocarriers, which possess biocompatibility, biodegradability, site-specificity, and stability, can help overcome existing biological barriers and deliver drugs to specific sites in the gastrointestinal tract.…”
Section: Current Treatment Regiments For Ibdmentioning
confidence: 99%
“…176 As reported by Wang et al, the gap between integrated systems and in vivo applications still needs more technical and scientific innovations. 177…”
Section: Cell Manipulationmentioning
confidence: 99%